“If we don’t take them off our streets, they’re going to continue to prey on innocent people.”: The discourse around recidivism and recidivists in the New York Times and the New York Post - Marko, Karoline (Linguistik Online, 2024)
Mass incarceration and high rates of recidivism in the United States have long been discussed in the scientific literature. A punitive culture has fostered harsh punishments and incarceration without considerable effects on recidivism rates. At the same time, research has indicated that rehabilitative measures and treatment programs for offenders have positive effects on their reintegration into society and help to reduce recidivism rates. In the present study, the discourse surrounding recidivism in the New York Times and the New York Post is investigated with a corpus of 666,290 words. The analyses indicate that the New York Times encourages a discussion of rehabilitative measures and adopts a view of recidivism that highlights recidivists’ potential for change. The New York Post, on the other hand, takes a more conservative approach and adopts a more dire view of recidivists, considering recidivism as a character trait rather than an indicator for the relative success of rehabilitation programs.